2017
DOI: 10.1016/j.jpainsymman.2016.12.342
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Neuropathy in Cancer Survivors

Abstract: Context Evidence suggests that chemotherapy-induced neuropathy (CIN) is a significant problem for cancer survivors. However, a detailed phenotypic characterization of CIN in cancer survivors is not available. Objectives To evaluate between group differences in demographic and clinical characteristics, as well as in measures of sensation, function, and postural control, in a sample of cancer survivors who received a platinum and/or a taxane-based CTX regimen and did (n=426) and did not (n=197) develop CIN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 99 publications
(110 reference statements)
12
82
0
2
Order By: Relevance
“…A total of 122 participants declined participation, and 67 did not complete the questionnaire. The study group consisted of 285 survivors of cancer during adolescence and young adulthood, with the mean age of 28 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and the control group consisted of 255 participants with the mean age of 28 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. There were no differences between the groups, except regarding education, where the controls had a significantly higher educational level than the cancer survivors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 122 participants declined participation, and 67 did not complete the questionnaire. The study group consisted of 285 survivors of cancer during adolescence and young adulthood, with the mean age of 28 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and the control group consisted of 255 participants with the mean age of 28 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. There were no differences between the groups, except regarding education, where the controls had a significantly higher educational level than the cancer survivors.…”
Section: Resultsmentioning
confidence: 99%
“…Having less frequent orgasm orgasms could lead to feeling less satisfied with sexual function. In studies on cancer survivors, one long-term effect is peripheral neuropathy in the extremities, and among female diabetes patients, having vascular damage and neuropathy may result in decreased genital blood flow and cause genital arousal, orgasm [32,33]. Whether difficulties having less frequent orgasm are due to physical or psychological effects needs further research, including more detailed information on cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Potential risk factors identified previously in the literature (Armstrong et al, ; Hauseer et al, ; Kaley & DeAngelis, ; Miaskowski et al, ; Ottaiano et al, ; Quasthoff & Hartung, ) were examined for their impact in the development of CIPN. These included: Diagnosis with acquired or hereditary neuropathy such as diabetes, renal disease, hypothyroidism, connective tissue disease.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Being obese and having more insomnia severity, anxiety, and depression were all associated with CIPN in other studies (Bao et al, ; Simon, Danso, Alberico, Basch, & Bennett, ). Older age, lower income, higher BMI, comorbidities, being born prematurely, higher cumulative dose of chemotherapy, and poorer functional status were also predictive of CIPN (Miaskowski et al, ). Diabetes was also shown to be predictor of CIPN (Ottaiano et al, ) although other studies have found no such link (Pereira et al, ; Simon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased distal lower extremity strength and loss of sensation, including proprioception, are risk factors for increased falls and balance deficits [812]. Patients who undergo treatment with taxane drugs and/or develop CIPN often present with decreased postural stability [1318,11]. Recent research suggests that CIPN may also be associated with functional impairments during ambulation [19].…”
Section: Introductionmentioning
confidence: 99%